Prevalence and Antimicrobial Resistance of ESBL E. coli in Early Broiler Production Stage and Farm Environment in Lithuania - Beatrice Kasparaviciene; Aleksandr Novoslavskij; Jurgita Aksomaitiene; Jurate Stankeviciene; Neringa Kasetiene; Romualdas Sinkevicius; Mindaugas Malakauskas (Microorganisms)
Escherichia coli, a major opportunistic pathogen in chickens, poses a serious threat to poultry production and public health via potential zoonotic transmission of ESBL-producing strains. Therefore, this study aimed to emphasize broilers as early carriers of ESBL E. coli and provide deeper insights into antimicrobial resistance of these bacteria. Prevalence and antimicrobial resistance (MIC) testing of ESBL E. coli in cloacal and environmental samples from one-day-old and five-day-old broilers was conducted on three different growth cycles from a conventional poultry farm in Lithuania. Confirmed prevalence of ESBL E. coli in cloacal samples ranged from 0% to 57.5%, and in environmental swabs from 0% to 25%. All 102 ESBL E. coli isolates were susceptible to meropenem, imipenem, fosfomycin, and colistin. However, 93.14% of the strains were resistant to ceftriaxone (89.06–100%, depending on bacteria isolation source), 97.06% to ciprofloxacin (95.31–100%), and 66.67% to tetracycline (26.09–100%). Additionally, 80.39% of ESBL E. coli strains exhibited multidrug resistance. In total, 23 different antimicrobial resistance profiles were confirmed, with CRO/AMS/AUG/CIP/SXT/TE and CRO/CIP being the most common, detected in 18 of the 102 strains. The detection of widespread antimicrobial-resistant ESBL E. coli in five-day-old broilers emphasizes the need to implement control strategies early in the broiler production cycle.